PENGEMBANGAN ALAT PEMBELAJARAN PASSING BAWAH BOLA VOLI SISWA KELAS V SD NEGERI 1 JARAKSARI - Dian Herlambang, Febry; Ratimiasih, Yulia; Kresnapati, Pandu (YLPK Mahardhika, 2024)
This research is based on the fact that many students still have not completed the KKM in the PJOK subject of volleyball under passing material at SD Negeri 1 Jaraksari, Wonosobo Regency. The learning process of bottom passing still uses conventional methods, there are no tools to make it easier for students to do bottom passing, so many bottom passes produced by students are still not good and correct. This research aims to create a volleyball hanger passing tool in volleyball, this learning aid is expected to help teachers so that learning activities are more effective and efficient. This research is a research and development (R&D). The sample of this study uses 2 validations, namely the validation of material experts and media experts. The subject of this study is students of SD Negeri 1 Jaraksari Wonosobo Regency with a small-scale trial of 14 students and a large-scale trial of 28 students. The data collection technique uses an instrument in the form of a questionnaire. The technical data analysis of this study is qualitative descriptive and quantitative percentage descriptive. The results of this study are assessed by the material as a whole aspect is